ACCOUNTABILITY OF THE REGIONAL HOUSE OF REPRESENTATIVES (DPRK) IN DEVELOPMENT OF LOCAL LEGISLATION PROGRAM - Ansarullah Ansarullah; Eddy Purnama; efendi efendi (Universitas Syiah Kuala, 2022)
This study aims to analyse and final the ideal legal design of the accountability concept to legislative organ in particular Regional House of Representatives (DPRK). One of The authority of DPRK is stated in Article 24 paragraph (1) of Law Number 11 of 2006 on the Government of Aceh states that: